The Great God of the Five Paths (Wudao Dashen 五道大神) in Early Medieval China - Chen, Frederick Shih-Chung (Journal of Chinese religions, 2018)
The Great God of the Five Paths, Wudao dashen 五道大神, in charge of rebirth in the Five Paths, has been one of the prominent otherworld bureaucratic deities in Chinese popular religion since the early medieval period. Wudao first appeared obscurely in certain Chinese Buddhist versions of the Buddha's biography, yet there is no mention of the deity in any Indic sources. As later medieval accounts record a popular sacrificial cult of Wudao outside of Orthodox Buddhist circles during the early medieval period and modern anthropological reports confirm that the deity was worshiped as a deity of popular religions rather than a Buddhist one, previous scholarship has been inclined to assume these parallels as possible evidence that a non-Buddhist sacrificial cult of the deity dated back to the early medieval era. This paper attempts to re-approach two issues related to the deity: its origin and the early development of its cult in early medieval China, before the Tang dynasty (618–907 C.E.). It first demonstrates a possible origin of the deity and its possible formation through a comparative research on the evolution of the various versions of the Buddha's biography in both Indic and Chinese contexts. A close examination of early medieval textual and archaeological sources, along with later medieval sources claiming the existence of a non-Buddhist sacrificial cult of Wudao dating back to the early medieval period, also reveals that Wudao was always presented or considered in a Buddhist-related context during the early medieval period, whereas primary later accounts of an early non-Buddhist cult are not supported by substantial evidence and were probably propagandistic stories made up by vegetarian reformist monks of the Tiantai School 天台宗 during the Song dynasty.